K-CONTINUOUS FUNCTIONS AND RIGHT B1 COMPOSITORS - Jonald P. Fenecios; Emmanuel A. Cabral (Journal of the Indonesian Mathematical Society, 2012)
pdf abstractDOI : http://dx.doi.org/10.22342/jims.18.1.108.37-44